Some novel effects in superconducting nanojunctions - Zaikin, A.D. (Фізико-технічний інститут низьких температур ім. Б.І. Вєркіна НАН України, 2004)
In this paper we address several new developments in the theory of dc Josephson effect in
superconducting weak links. We analyze an interplay between quantum interference effects and
Andreev reflection in SNS nanojunctions with insulating barriers and demonstrate that these effects
may qualitatively modify the Josephson current in such structures. We also investigate an impact
of the parity effect on persistent currents in superconducting nanorings interrupted by a quantum
point contact (QPC). In the limit of zero temperature and for the odd number of electrons in
the ring we predict complete suppression of the supercurrent across QPC with one conducting
mode. In nanorings with SNS junctions a π-state can occur for the odd number of electrons.
Changing this number from even to odd yields spontaneous supercurrent in the ground state of
such rings without any externally applied magnetic flux.